"And David's sons were priests": Translating Perceived Discrepancies. Issue 3 (December 2021) - de Regt, Lénart J.
Second Samuel 8.18 mentions that David's sons were priests. This statement has puzzled translators for a long time. How could David's sons be priests, since they were of the tribe of Judah and not descendants of Aaron? It may be tempting to follow KJV or NIV or other influential translations and say that they were "chief rulers" or "royal advisors." But this will take us away from the Hebrew text. To say that in 2 Sam 8.18 we should translate "priests" because we translate from the Hebrew and this is what the Hebrew says, so that other renderings are incorrect, is a valid response. But how could the statement in 2 Sam 8.18 and its context be explained more satisfactorily? And how can translation teams be advised when David's sons are not priests in their drafted translation of this verse?